Insight into the atomic structure of Li2MnO3 in Li-rich Mn-based cathode materials and the impact of its atomic arrangement on electrochemical performance. Issue 22 (24th May 2017) - Song, Yuanzhe; Zhao, Xuebing; Wang, Chao; Bi, Han; Zhang, Jie; Li, Sesi; Wang, Min; Che, Renchao
Abstract : Local heterogeneity in crystal lattice is directly observed in synthesized Li2 MnO3 /LiMO2 (M = Ni, Mn) cathode materials. With SAED application, for the first time, we accordingly uncover that the lattice heterogeneity is induced by different Li2 MnO3 atomic arrangements coexisting in same crystal domain. Abstract : Li-rich Mn-based cathode materials have been considered as promising candidates for next generation Li-ion batteries due to their high-energy density, low cost and non-toxicity. However, the atomic arrangement of such materials and the relationship between the microstructure and electrochemical performance are still not fully understood. In this paper, local heterogeneity in the crystal lattice is directly observed in synthesized Li2 MnO3 /LiMO2 (M = Ni and Mn) cathode materials. With SAED application, for the first time, we accordingly uncover that the lattice heterogeneity is induced by different Li2 MnO3 atomic arrangements coexisting in the same crystal domain. The co-growth of Li2 MnO3 with different orientations is proved to be a defective feature, which would induce atomic vacancy concentration in the lattice and increase the risk of layered structure collapse in the cycling process. The electrochemical test results also suggest that the composition with a relatively uniform Li2 MnO3 arrangement exhibits better cycling performance (the capacity retention is as high as 95.1% after 50 cycles at 0.1C), oppositely, the coexistence of multiple complex Li2 MnO3 arrangements results in poor cycling performance (the capacity retention is below 70% after 50 cycles at 0.1C). The crystal lattice structure comparison between primary and cycled is shown to manifest the effect of Li2 MnO3 arrangement on the electrochemical performance and structural stability, providing one possible explanation for the capacity degradation of the Li-rich materials.